2013
DOI: 10.1136/gutjnl-2013-305997
|View full text |Cite
|
Sign up to set email alerts
|

Acid-suppressive medications and risk of oesophageal adenocarcinoma in patients with Barrett's oesophagus: a systematic review and meta-analysis

Abstract: Background and aims Acid-suppressive medications, particularly proton pump inhibitors (PPIs), may decrease the risk of oesophageal adenocarcinoma (OAC) in patients with Barrett’s oesophagus (BO). We performed a systematic review with meta-analysis of studies evaluating the association between acid-suppressive medications (PPIs and histamine receptor antagonists (H2RAs)) and risk of OAC or high-grade dysplasia (BO-HGD) in patients with BO. Methods We performed a systematic search of multiple electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
165
3
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(186 citation statements)
references
References 43 publications
5
165
3
8
Order By: Relevance
“…A metaanalysis based on 7 studies with 2,813 patients demonstrated a 71% reduced risk of HGD and/or EAC with PPI users (OR 0.3, 95% CI 0.1-0.8). No signifi cant eff ect was shown for H 2 RA usage in two studies ( 57 ). In another meta-analysis of 9 observational studies of 5,446 participants (605 with HGD or EAC), usage of cyclooxygenase inhibitors, aspirin, and nonaspirin cyclooxygenase inhibitors was associated with reduced risk for HGD and EAC independent of duration of therapy ( 58 ).…”
Section: Summary Of Evidencementioning
confidence: 96%
See 2 more Smart Citations
“…A metaanalysis based on 7 studies with 2,813 patients demonstrated a 71% reduced risk of HGD and/or EAC with PPI users (OR 0.3, 95% CI 0.1-0.8). No signifi cant eff ect was shown for H 2 RA usage in two studies ( 57 ). In another meta-analysis of 9 observational studies of 5,446 participants (605 with HGD or EAC), usage of cyclooxygenase inhibitors, aspirin, and nonaspirin cyclooxygenase inhibitors was associated with reduced risk for HGD and EAC independent of duration of therapy ( 58 ).…”
Section: Summary Of Evidencementioning
confidence: 96%
“…However, even in patients without refl ux symptoms, in whom BE is incidentally found during evaluation of other symptoms and/or signs, the use of PPIs deserves consideration. Several cohort studies now suggest that subjects with BE maintained on PPI therapy have a decreased risk of progression to neoplastic BE compared with those with either no acid suppressive therapy or those maintained on H 2 RA therapy ( 57,(137)(138)(139). In addition, the risk profi le of these medications is favorable in most patients, and the cost of this class of drugs has diminished substantially in recent years because of the availability of generic forms of the medications.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it is recommended that patients with BE should receive proton pump inhibitors (PPI) as part of the therapy. Moreover, several studies have shown that patients on PPI's have a lower risk of neoplastic progression compared to patients without acid suppressive therapy (52,53).…”
Section: Management and Treatment Of Bementioning
confidence: 99%
“…2,3 Yet, once BO is installed, PPIs have been associated with a significant decrease in highgrade dysplasia and OAC arising from BO. 4,5 Second, Masclee et al outline that, in contrast to BO, the OAC incidence rate continued to increase until now, which may reflect the long lag time between BO and high-grade dysplasia and OAC. Another hypothesis may be raised: as no evidence of BO is found in most cases of incident diagnoses of OAC, 6,7 at least part of these might arise from high-grade dysplasia developed in specific intestinal metaplasia in the gastric cardia, at the anatomical gastro-oesophageal junction (GOJ) and without evidence of classical or short-segment BO.…”
mentioning
confidence: 99%